2017
DOI: 10.1371/journal.pone.0174521
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of silver cations onto Lactococcus lactis and Lactobacillus casei isolated from dairy products

Abstract: The current work deals with the phenomenon of silver cations uptake by two kinds of bacteria isolated from dairy products. The mechanism of sorption of silver cations by Lactococcus lactis and Lactobacillus casei bacteria was investigated. Inductively coupled plasma–mass spectrometry (ICP-MS) was used for determination of silver concentration sorbed by bacteria. Analysis of charge distribution was conducted by diffraction light scattering method. Changes in the ultrastructure of Lactococcus lactis and Lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 70 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…The synthesis of ZnO nanomaterials can be carried out by using various types of biological sources such as proteins, plant extracts or microorganisms. Recent studies have demonstrated that both intra- and extracellular approaches are efficient enough to synthesize different types of nanoparticles, e.g., silver [ 10 , 27 , 32 ], gold [ 33 ] or titanium oxide [ 34 ] NPs; however, the microbial synthesis of nan-ZnO has still not been sufficiently described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of ZnO nanomaterials can be carried out by using various types of biological sources such as proteins, plant extracts or microorganisms. Recent studies have demonstrated that both intra- and extracellular approaches are efficient enough to synthesize different types of nanoparticles, e.g., silver [ 10 , 27 , 32 ], gold [ 33 ] or titanium oxide [ 34 ] NPs; however, the microbial synthesis of nan-ZnO has still not been sufficiently described.…”
Section: Resultsmentioning
confidence: 99%
“…For the extracellular synthesis of ZnO NCs, the Lactobacillus paracasei LPC20, from the collection of Centre for Modern Interdisciplinary Technologies, Nicolaus Copernicus University in Toruń, isolated from sweet whey (Dairy Cooperative in Drzycim, Drzycim, Poland) [ 27 ], was chosen. The L. paracasei LPC20 strain was grown on Müller–Hinton broth (MH, Sigma-Aldrich, St. Louis, MO, USA) and incubated at 37 °C for 24 h. After the incubation, the culture was centrifuged at 12,000 rpm for 30 min and the cell-free supernatant was collected and used for further ZnO NC synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…The Lactobacillus paracasei and Lactococcus lactis strains were isolated from dairy products (Dairy Cooperative in Drzycim, Poland), according to Milanowski et al [50]. The 16S rDNA nucleotide sequences of L. paracasei LB3 and L. lactis 56 have been submitted in GenBank and deposited in the Polish Collection of Microorganisms (PCM) under deposit no.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that some lactic acid bacteria (LAB) strains, including L. rhamnosus , L. plantarum , and Leuconostoc mesenteroides, are capable of binding and removing heavy metals, such as silver, cadmium and lead in vitro [ 19 , 20 , 21 ]. Furthermore, various recent studies have revealed that LAB can effectively protect against metal-induced oxidative stress through antioxidation in vivo [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%